Work Life Balance, Turnover Intention, And Organizational Commitment in Nursing Employees at X Hospital, Tangerang, Indonesia - Muhamad Chudri Wardana; Rina Anindita; Ratna Indrawati (Penerbit Kemala Indonesia, 2020)
Work Life Balance was one factors could influence employee’s performance. Conflicts between work and personal life could increase stress levels which could reduce employee morale, causing decreased job satisfaction which triggered employee intentions to leave. Turnover Intention (TI) was often associated with Organizational Commitment (OC) and Work Life Balance (WLB). Study aims to determine the influence of WLB on TI through OC as intervening variable on nursing employees in one private hospital in Tangerang. This causality research with quantitative approach, carried out one stage through the Survey method. The population as well as sample of 79 nurses and midwives as saturated sample. Through path analysis, WLB has significant positive influence on TI. WLB has significant positive influence on OC, OC doesn’t directly influence on TI, WLB and OC together have significant positive influence on TI, and OC isn’t intervening variable between WLB and TI. This situation is assumed due to the demographic factors’ majority young respondents under 25 years old, and high level of need for nurses around hospital. Managerial implications, Hospital management needs to reduce TI with variety of Human Resources management programs, including selective recruitment, creating conducive work atmosphere and identifying other factors that influence the increasing TI.